Analisis Yuridis Atas Penggabungan PT Taspen (Persero) dan PT Asabri (Persero) pada Badan Penyelenggara Jaminan Sosial - Putra, Wahyudi Prima; Suhaidi, Suhaidi; Leviza, Jelly; Marsella, Marsella (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
The transformation becomes an important vocabulary since last seven years in Indonesia, precisely since the enactment of the National Social Security System (Social Security Act) on October 19, 2004.Â  Persero four state-owned social security program organizers PT Askes, PT Asabri, PT Jamsostek and PT TaspenÂ  will be transformed into BPJS . Asabri program is part of the rights of soldiers and police members on a decent income. Asabri programs and programs pension payments transferred by Asabri PT and old age savings program and programs pension payments transferred from TASPEN PT is part of the program in accordance with that law. With the inclusion of informal workers in the social security system which has clearly not been recorded, it will take time and a very large cost.